Peningkatan Pengetahuan Smart Home dan Penerapan keamanan Pintu Otomatis - Fera Lestari; Dian Pratiwi; Novia Utami Putri; Ria Oktaviani Sinia (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
The door is an important component of the dwelling. The need for security is an important thing in everyday life. Home security such as doors, cupboards, lockers and so on at this time still uses a manual system, namely by using conventional keys. Conventional door locks usually consist of a key housing and a saddle to open it. The demands that must be carried out by schools in implementing the learning process that utilize information and communication technology face various obstacles that are not simple. The importance of technology-based learning that can open students' horizons and hone students' soft skills. The implementation of the PKM Assisted School activities is carried out through three stages, namely the initial stage, the process stage, and the final stage. The implementation of training on making door locks begins with the provision of smart home and door lock materials to open up insights about automation technology. After participants gain an understanding of smart homes and door locks, participants will be shown the components and systems in making door locks. Furthermore, each participant will do practice to make an automatic door security system so that participants gain experience in making automatic lock systems. Furthermore, the participants are required to be able to run an automatic security system by designing a security lock using a numeric password until the system is successfully run. The increase in skills and knowledge related to door locks can be seen from the participation of each participant with the successful creation of a door lock system by each group. From the results of the questionnaires that have been filled out by students, 89% stated that they have gained new knowledge related to the manufacture of door lock systems.